EXTRACURRICULAR MUSICAL ACTIVITIES IN SECONDARY SCHOOLS - Madaminov Nasimjon Kholjouraevich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
this article will further improve the quality of education through extracurricular musical activities. The child will be able to think freely in training, openly demonstrate creativity, create conditions in a circle for a child to have meaningful free time after school lessons, circle training will allow the child to work on himself, be able to engage in the direction in which he is interested, gain additional knowledge. During the training, together with the lesson, children Exchange creative experiences with each other. Looking in one direction, future young specialists are formed. A circle can replace a circle according to the fact that children freely choose the circles themselves, attend several circles at the same time and are interested. It is reported that in the future children will serve as a starting step in the choice of a single profession .